Experimental investigation of consecutive water droplets falling down through high-temperature gas zone; International Journal of Heat and Mass Transfer; Vol. 95 - Volkov R. S. Roman Sergeevich; Kuznetsov G. V. Geny Vladimirovich; Legros J. C. Jean Claude; Strizhak P. A. Pavel Alexandrovich (2016, 2016)
Title screen